Quality Control Analysis of Mozzarella Cheese Coagulation Process in CV “XYZ” - Achmad Wahyu Hidayat; Jariyah; Alfiya Dewi Novanda (Nusantara Science and Technology Proceedings, 2022)
Cheese is a dairy product high in nutrients that are prone to damage. One type is mozzarella cheese which has a smooth, soft, and filamentous texture. One of the crucial steps in cheese processing is the coagulation process of milk which is the process of clotting milk and producing curd and whey. One of the critical things that need to do to retain the cheese quality is to conduct a quality control analysis of the coagulation process. Quality control is the process of producing healthy food. CV “XYZ” is a company engaged in milk processing in East Java. The indicators that are important to note in the coagulation process are whey pH, curd weight, and curd yield to obtain good cheese quality in CV “XYZ”. The method used is a direct observation which includes sampling, measuring whey pH, weighing curd weight, calculating curd yield, and data processing. The results obtained in quality control during the coagulation process of mozzarella cheese in CV “XYZ” are whey pH, weight, and curd yields show controlled values because none of them exceed the limits set by the company. Sampling on day 10 had the best pH value of whey, with a value of 5.13. The best weight and yield of the cheese curd were found in the 4th-day sampling, which weigh 123.6kg and the yield 12.06%. The factors that cause the difference in the pH value of whey are the initial pH value of milk and the addition of acidifier types. The factors that cause the differences in weight yield and curd yield are the nutritional content of milk, the pH of milk after acidification, the addition of CaCl2, and the time of coagulation.